PENGARUH MEDIA PLAYDOUGH TERHADAP PERKEMBANGANKOGNITIF ANAK USIA 5 - 6 TAHUN DI TK WIDYA KUMARA SANTHI KECAMATAN BANJAR KABUPATEN BULELENG - I Made Hartawan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2020)
The purpose of this research is to find out whether there is an influence of media play on the cognitive development of children aged 5-6 years at Widya Kumara Santhi Kindergarten, Banjar District, Buleleng Regency 2016/2017 Academic Year. Playdough is one activity that is beneficial for the development of a child's brain. Cognitive development is a change in thinking or intellectual abilities. According to Minister of Education Regulation no. 58 of 2009 revealed that one aspect of cognitive development that needs to be developed in children aged 5-6 years is the concept of shape, color, size, and pattern. Shapes taught to young children are geometric shapes such as circles, triangles, squares and rectangles. This type of research is using a quantitative approach, the target of this study is 30 children aged 5-6 years at TK Widya Kumara Santhi, Banjar District, Buleleng Regency. From the results of quantitative research using Pre Experiments with the type of one group pre-test and post-test desaign. Based on the results of the t test, the significance value (sig) was 0,000. The significance value of the t test is smaller than the maximum limit set at 0.05 (sig ≥ 0.05) so that it can be concluded if there are significant differences in the cognitive development of children before and after using media play. From the results of the paired sample t test, it can be concluded that media play has an effect on cognitive development (Ha accepted). With the acceptance of the working hypothesis it can be concluded that the media playdough has a quite high influence on the Cognitive Development of Children Aged 5-6 Years at Widya Kumara Santhi Kindergarten, Banjar District, Buleleng Regency.